(untitled) (Journal of Solar Energy Research Updates, 2022)
Abstract: In recent years, the fixed bed dehumidification system has received extensive attention. Research shows that the fixed bed can be combined with the vapor compression refrigeration system to replace the traditional air conditioning (A/C) system, improve the dehumidification efficiency of the system and reduce energy consumption of A/C. In this study, the optimization and improvement methods of the fixed bed dehumidifier in recent years are introduced in detail firstly. It points out that adding heating/cooling devices to the fixed bed can greatly improve the dehumidification capacity and efficiency of the system, which is the main method to improve the fixed bed currently; Optimizing the structure of fixed bed is also an effective method, but the current research results have limited improvement on dehumidification performance; Optimizing the regeneration mode of fixed bed can improve the utilization rate of renewable energy and improving the overall dehumidification efficiency of the system, but the research in the direction is still insufficient; The parallel double packed bed structure can ensure the continuous operation of the fixed bed to improve the dehumidification efficiency of the system, but such systems are large in scale and high in cost. Then the dehumidification performances of various systems are summarized and comprehensively compared. Finally, the future optimization and improvement direction of the fixed bed is pointed out.